Chlorine dioxide against bacteria and yeasts from the alcoholic fermentation - Meneghin, Silvana Perissatto [UNESP]; Reis, Fabricia Cristina; De Almeida, Paulo Garcia; Ceccato-Antonini, Sandra Regina (FapUNIFESP (SciELO), 2008)
The ethanol production in Brazil is carried out by fed-batch or continuous process with cell recycle, in such way that bacterial contaminants are also recycled and may be troublesome due to the substrate competition. Addition of sulphuric acid when inoculum cells are washed can control the bacterial growth or alternatively biocides are used. This work aimed to verify the effect of chlorine dioxide, a well-known biocide for bacterial decontamination of water and equipments, against contaminant bacteria (Bacillus subtilis, Lactobacillus plantarum, Lactobacillus fermentum and Leuconostoc mesenteroides) from alcoholic fermentation, through the method of minimum inhibitory concentration (MIC), as well as its effect on the industrial yeast inoculum. Lower MIC was found for B. subtilis (10 ppm) and Leuconostoc mesenteroides (50 ppm) than for Lactobacillus fermentum (75 ppm) and Lactobacillus plantarum (125 ppm). Additionally, these concentrations of chlorine dioxide had similar effects on bacteria as 3 ppm of Kamoran® (recommended dosage for fermentation tanks), exception for B. subtilis, which could not be controlled at this Kamoran® dosage. The growth of industrial yeasts was affected when the concentration of chlorine dioxide was higher than 50 ppm, but the effect was slightly dependent on the type of yeast strain. Smooth yeast colonies (dispersed cells) seemed to be more sensitive than wrinkled yeast colonies (clustered cells/pseudohyphal growth), both isolated from an alcohol-producing unit during the 2006/2007 sugar cane harvest. The main advantage in the usage of chlorine dioxide that it can replace antibiotics, avoiding the selection of resistant populations of microorganisms.
Keywords: Alcohol; Antibacterial agent; Bacteria; Chlorine dioxide; Fermentation; Yeast